Exploring English Idioms in the Song Lyrics of the "Cannot Be, Whatsoever" Album by Novo Amor - Aditya, Tasya Devi; Faiza, Dinar; Wulandari, Yasinta (Educalitra: English Education, Linguistics, and Literature Journal, 2023)
This research aimed to find the types of idioms in the song lyrics of the Cannot Be, Whatsoever album by Novo Amor. This research used descriptive research with synchronic linguistics analysis. The researcher analyzed 9 (nine) songs. They are Opaline, I Feel Better, Decimal, No Plans, Birdcage, Keep Me, Halloween, If Were Being Honest, and Guest Book. The researcher analyzed the idiomatic expression types using the theory of Makkai (1994), which classifies the idioms based on their structure. Besides that, the researcher used idiom similarity in the idiom dictionary to find the meaning of the idioms. From the analysis, the researcher found 63 idiomatic expressions in the song lyrics of the songs in the Cannot Be, Whatsoever album by Novo Amor. The idiom types according to Makkais theory that was found in this album were 10 Phrasal Verb Idioms, 44 Tournure Idioms, 1 Irreversible Binomial Idioms, and 8 Phrasal Compound Idioms. It can be said that the dominant type of Makkais theory in this albums songs is the Tournure Idiom, and the least type is the Irreversible Binomial Idiom.